Intracellular Ca2+ signalling: unexpected new roles for the usual suspect - Moccia, Francesco; Fiorio Pla, Alessandra; Lim, Dmitry; Lodola, Francesco; Gerbino, Andrea (Frontiers in Physiology, 2023)
Cytosolic Ca2+ signals are organized in complex spatial and temporal pattern that underlie their unique ability to regulate multiple cellular functions. Changes in intracellular Ca 2+ concentration ([Ca2+]i) are finely tuned by the concerted interaction of membrane receptors and ion channels that introduce Ca2+ into the cytosol, Ca2+-dependent sensors and effectors that translate the elevation in [Ca2+]i into a biological output, and Ca2+ -clearing mechanisms that return the [Ca2+]i to pre-stimulation levels and prevent cytotoxic Ca2+ overload. The assortment of the Ca2+ handling machinery varies among different cell types to generate intracellular Ca2+ signals that are selectively tailored to subserve specific functions. The advent of novel high-speed, 2D and 3D time-lapse imaging techniques, singlewavelength and genetic Ca2+ indicators, as well as the development of novel genetic engineering tools to manipulate single cells and whole animals, has shed novel light on the regulation of cellular activity by the Ca2+ handling machinery. A symposium organized within the framework of the 72 nd Annual Meeting of the Italian Society of Physiology, held in Bari on 14-16 th September 2022, has recently addressed many of the unexpected mechanisms whereby intracellular Ca2+ signalling regulates cellular fate in healthy and disease states. Herein, we present a report of this symposium, in which the following emerging topics were discussed: 1) regulation of water reabsorption in the kidney by lysosomal Ca2+ This is a provisional file, not the final typeset article release through Transient Receptor Potential Mucolipin 1 (TRPML1); 2) endoplasmic reticulum-tomitochondria Ca2+ transfer in Alzheimer's disease-related astroglial dysfunction; 3) the non-canonical role of TRP Melastatin 8 (TRPM8) as a Rap1A inhibitor in the definition of some cancer hallmarks; and 4) non-genetic optical stimulation of Ca2+ signals in the cardiovascular system.